Pengaruh Tarif dan Kualitas Layanan terhadap Kepuasan Pelanggan melalui Citra Merek pada Pengguna Grab di Jakarta - Altito, Muhammad Lutfi; Mohamad Rizan; Shandy Aditya (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study aims to analyze the effect of fare and service quality on customer satisfaction mediated by brand image among Grab users in Jakarta, focusing on how customers’ perceptions of pricing and service shape brand impressions that ultimately influence their level of satisfaction. This research employs a quantitative approach with the Structural Equation Modeling (SEM) method using SmartPLS software. The sampling technique used is purposive sampling with a total of 264 respondents. The results show that fare and service quality have a positive and significant effect on brand image. Fare and service quality also have a positive and significant effect on customer satisfaction. Brand image has a positive and significant effect on customer satisfaction and mediates the effect of fare and service quality on customer satisfaction.